Hubungan Keterbukaan Diri dengan Interaksi Sosial Peserta Didik d Sekolah Menengah Pertama Minhajuth Thullab Way Jepara Lampung Timur - Maharani, Laila; Hikmah, Latifatul (Universitas Islam Negeri Raden Intan Lampung, 2015)
This research method used correlation quantitative research using cross sectional approach. The study population is class VII Integral Minhajuth Thullab junior a number of 70 students then the simpling technique used is purposive sampling, the sample was selected as many as 24 students of class VIIB. Data collection techniques used were questionnaires, observations and interviews. The results showed 20 (83.3%) of the students had low social interaction and there were 18 students (75.1%) who had a closed attitude. While pserta students (16.7%) who have a high social interaction. The result of the analysis shows that there is a significant correlation between self-disclosure with social interaction of students of class VIIB. Suggestions asked by the researchers for the school is to facilitate the needs of learners and teachers counseling guidance to recommend space for conducting a counseling session in order to help learners. And especially for guidance and counseling teachers to be able to create counseling guidance services program, especially personal and social problems either by personal or group service.